Mitochondrial dysfunction in liver failure requiring transplantation. Issue 3 (6th April 2016) - Lane, Maria; Boczonadi, Veronika; Bachtari, Sahar; Gomez‐Duran, Aurora; Langer, Thorsten; Griffiths, Alexandra; Kleinle, Stephanie; Dineiger, Christine; Abicht, Angela; Holinski‐Feder, Elke; Schara, Ulrike; Gerner, Patrick; et al.
Abstract: Liver failure is a heterogeneous condition which may be fatal and the primary cause is frequently unknown. We investigated mitochondrial oxidative phosphorylation in patients undergoing liver transplantation. We studied 45 patients who had liver transplantation due to a variety of clinical presentations. Blue native polyacrylamide gel electrophoresis with immunodetection of respiratory chain complexes I‐V, biochemical activity of respiratory chain complexes II and IV and quantification of mitochondrial DNA (mtDNA) copy number were investigated in liver tissue collected from the explanted liver during transplantation. Abnormal mitochondrial function was frequently present in this cohort: ten of 40 patients (25 %) had a defect of one or more respiratory chain enzyme complexes on blue native gels, 20 patients (44 %) had low activity of complex II and/or IV and ten (22 %) had a reduced mtDNA copy number. Combined respiratory chain deficiency and reduced numbers of mitochondria were detected in all three patients with acute liver failure. Low complex IV activity in biliary atresia and complex II defects in cirrhosis were common findings. All six patients diagnosed with liver tumours showed variable alterations in mitochondrial function, probably due to the heterogeneity of the presenting tumour. In conclusion, mitochondrial dysfunction is common in severe liver failure in non‐mitochondrial conditions. Therefore, in contrast to the common practice detection of respiratory chain abnormalities in liver should not restrict the inclusion of patients for liver transplantation. Furthermore, improving mitochondrial function may be targeted as part of a complex therapy approach in different forms of liver diseases.